PENINGKATAN HASIL BELAJAR KOGNITIF IPA FISIKA SISWA DENGAN JOYFUL LEARNING DI KELAS VII SMPN 3 XIII KOTO KAMPAR - Susilawati '; Muhammad Nasir; Hendar Sudrajat (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrck: This research aims to determine the increase in cognitive science physics learning achievement of students with joyful learning. This research was conducted in SMPN 3 XIII Koto Kampar in August 2015. This research subject is 20 students of class VIIa as a control group with conventional learning and 21 students of class VIIb as an experimental group class with joyful learning. This research is pre-experimental design forms Intact Group Comparison. Instrument of collecting data in this research is a cognitive achievement test consisting of 10 multiple choice items. Descriptive analysis of the results obtained by the average absorption and effectiveness of learning of students in the experimental class of 80% and 70.5% control class with high category and effective. Mastery learning classical to experimental class categorized due to the percentage of 90.47%, while the control group did not complete with percentage of 70%. Completeness of indicators competency achievement in the experimental class of 100% and 70% control class declared complete. The results of inferential analysis through the sign test obtained a value of tcount>ttable (2,897>2,023), which means there is improvement of the cognitive learning science Physics with joyful learning of the use of conventional learning. It can be concluded with joyful learning can improve cognitive achievement of students of class VII SMPN 3 XIII Koto Kampar in the subject matter temperature and measurement.Key Words: The cognitive learning, Joyful Learning, Descriptive Analysis and Analysis Inferential